Lean Six Sigma to Improve Emergency Medicine Time management - Taha, Mazen (2018)
Acute thromboembolic diseases are acute emergencies that can cause permanent damage to tissues and are the leading causes for mortalities worldwide. Management of these cases is strictly time driven and has a narrow range to move within. Acute myocardial infarction and acute ischaemic stroke were the concern of this study. Based on the concept of waste reduction and preventing errors the combined Lean and Six Sigma approach was used. Empowerment of the dedicated teams was an essential step towards the improvement of the process. The process revision removed all non-added value steps and simplified the process. There was a 100% compliance with the target for the management of acute ST-segment elevation myocardial infarction and 50% compliance with acute stroke management targets. New ideas are prone to be used while designing new hospitals. Planning for sustainability and corporate social responsibility is needed to improve the clinical outcomes. More efforts are needed to produce the cultural changes in the community for better outcomes.